2009
DOI: 10.1148/radiol.2512081548
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Disorders: Focally Altered Cerebral Perfusion Measured with Arterial Spin-labeling MR Imaging

Abstract: This study revealed alterations of regional perfusion in the brains of patients with RDD that differed from those in patients with NDD. These results are consistent with the concept that RDD is associated with decreased activity of the bilateral prefrontal areas; and NDD, with decreased activity of left frontal areas in conjunction with overactivity of the bilateral limbic system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
74
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 109 publications
(92 citation statements)
references
References 52 publications
(62 reference statements)
17
74
0
1
Order By: Relevance
“…Concomitantly, previous MRIbased perfusion studies in adults did not find rCBF differences between healthy controls and patients with MDD in this region. 37,54 In another report, only patients with poor treatment response exhibited hypoperfusion of the ACC, 36 indicating that lower cingulate blood flow may be associated with drug-related clinical outcomes. In accordance with our present findings, a recent transdiagnostic study reported lower ACC blood flow in adult patients with MDD than in healthy controls and patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Concomitantly, previous MRIbased perfusion studies in adults did not find rCBF differences between healthy controls and patients with MDD in this region. 37,54 In another report, only patients with poor treatment response exhibited hypoperfusion of the ACC, 36 indicating that lower cingulate blood flow may be associated with drug-related clinical outcomes. In accordance with our present findings, a recent transdiagnostic study reported lower ACC blood flow in adult patients with MDD than in healthy controls and patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Nonmedi cated patients may present prefrontal hypoperfusion when measured with ASL. 33,36 Major depressive disorder has been repeatedly associated with brain volume change. 19,20,21,[22][23][24] Volume reduction of the ACC, as found in our medicated patient subsample, is a robust finding in patients with MDD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The living quarters of all the participants were within 6.5 miles of our hospital, and all of them could keep in touch with their families by cell phone. Healthy controls were scanned for other studies 10,11 shortly (range 7-56, mean 41 [SD 14] d) before the earthquake.…”
Section: Discussionmentioning
confidence: 99%
“…They were recruited by poster advertisement, and they had undergone MRI for other studies 10,11 shortly before the earthquake. The following exclusion criteria applied to both groups: the existence of any neurologic or psychiatric disorder, any recent medications known to affect brain function, alcohol or drug abuse, pregnancy or any systemic physical illness, such as hepatitis or diabetes.…”
Section: Participantsmentioning
confidence: 99%